(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-4-86-94 Abstract. This article explores the representation of the female character in “Tajalli” (“Manifestation”), a short story from “The Stray Dog” collection by the Iranian writer Sadegh Hedayat. In this story, Hedayat employs his distinct literary style to depict the life of an Armenian woman named Hasmik, living in the patriarchal society of early 20th-century Iran. Through a psychological examination of Hasmik’s inner world and her struggle between personal desires and social constraints, the narrative reveals the underlying mechanisms of female oppression. The study critically investigates how the story addresses issues of gender, family traditions, love, and the fate of women. Special attention is given to the absent figure of the husband, who, despite not appearing directly in the plot, symbolizes the dominant patriarchal order. The article also considers the influence of Russian and Western literature on the development of Hedayat’s artistic worldview. In conclusion, the paper highlights the importance of comparative literary studies and the representation of female characters in Persian literature as vital tools for understanding the status of women within the socio-cultural context of modern Iran. Key words: Sadegh Hedayat, Persian literature, Iran, “Tajalli”, women’s status, Hasmik